2003
DOI: 10.1016/s0304-3959(03)00249-5
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of central itch modulation in the human brain using positron emission tomography

Abstract: The unpleasantness of itching is reduced by cooling. Although previous research suggests the presence of a central itch modulation system, there is little documentation about the modulation system in the brain. In the present study, we investigated the modulating system of the itching sensation in human brains using positron emission tomography and H(2) (15)O. The significant increases of regional cerebral blood flow caused by histamine stimuli using iontophoresis were observed in the anterior cingulate cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
146
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 38 publications
13
146
1
6
Order By: Relevance
“…[68,69,78] The periaqueductal grey (PAG) belongs to the descending inhibitory pain controls, but there is some evidence from animal studies and a previous PET study that it also inhibits itch. [68,109,110] Data from fMRI studies with healthy subjects, however, are contradictory: in one study, the PAG was activated during scratching, in response to an electrical itch stimulus, [92] whilst in another study, using cowhage, a deactivation of the PAG during scratching was observed. [91] Animal studies demonstrated that apart from this top-down inhibition, ascending itch signals are also suppressed on a spinal level.…”
Section: Central Mechanisms Of Itch Inhibitionmentioning
confidence: 98%
“…[68,69,78] The periaqueductal grey (PAG) belongs to the descending inhibitory pain controls, but there is some evidence from animal studies and a previous PET study that it also inhibits itch. [68,109,110] Data from fMRI studies with healthy subjects, however, are contradictory: in one study, the PAG was activated during scratching, in response to an electrical itch stimulus, [92] whilst in another study, using cowhage, a deactivation of the PAG during scratching was observed. [91] Animal studies demonstrated that apart from this top-down inhibition, ascending itch signals are also suppressed on a spinal level.…”
Section: Central Mechanisms Of Itch Inhibitionmentioning
confidence: 98%
“…The supraspinal processing of itch and its corresponding scratch response in humans have recently been investigated by functional PET (fPET) and functional MRI (fMRI). Here induction of itch by histamine application coactivates the anterior cingulate and insular cortex, premotor and supplementary motor areas, cerebellum, primary somatosensory cortex, and thalamus (40)(41)(42). As done earlier for pain sensation, particular aspects of the itch sensation have been correlated with the activation of certain brain areas: spatial and temporal aspects may be processed in the primary somatosensory cortex, planning of the scratch response in the premotor and supplementary motor cortices, and affective and motivational aspects in the anterior cingulate (38,43) and insular cortex ( Figure 2).…”
Section: Figurementioning
confidence: 99%
“…When the modulation of itch by painful cold stimuli was examined by fPET, the periaqueductal gray matter was activated only when painful and itching stimuli were applied simultaneously (42). This activation was combined with reduced activity in the anterior cingulate, dorsolateral prefrontal cortex, and parietal cortex.…”
Section: Figurementioning
confidence: 99%
“…Itch is an unpleasant sensation that elicits the desire to scratch and, as with chronic pain, can be deleterious (1-5). Itch can be triggered by exogenous (e.g., allergens, toxins, medication, illegal drugs, microbes) or endogenous (e.g., amines, proteases, neuropeptides, cytokines, prostanoids) stimuli (4) that transmit signals via C fibers to the central nervous system (3,(6)(7)(8)(9)(10)(11)(12)(13). While the existence of itchselective C fibers in the sensory nervous system appears to be generally acknowledged (6,7), the neuronal regulatory circuits and the signaling pathways of itch in both the peripheral and central nervous systems, including potential endogenous antipruritic mechanisms, are still mostly unknown (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%